Resolution MEPC.384 (81): Is It the Answer? - Soediono, Felix Abraham (Jurnal Ragam Pengabdian, 2026)
The increasing number of containers lost at sea has become a growing concern in international maritime law due to its hazardous nature towards marine environmental and navigational activity. Prior to 2026, the international legal framework under the International Convention for the Prevention of Pollution from Ships (MARPOL) and the International Convention for the Safety of Life at Sea (SOLAS) did not comprehensively regulate the reporting of container loss incidents unless there is harmful substances involved or immediate navigational dangers. This article examines the legal significance of Resolution MEPC.384(81), which amended Protocol I of MARPOL and entered into force on 1 January 2026. Using normative legal research with statutory approaches, this article analyses relevant international conventions, IMO resolutions, MSC & MEPC Reports, and related legal literatures. The study finds that the amendment represents an important normative development by expanding mandatory reporting obligations to include all container losses regardless the cargo classification. The amendment also strengthens the relationship between MARPOL and SOLAS by treating container loss simultaneously as a marine environment threat and a navigational hazard. However, the study argues that the effectiveness of the amendment remains dependent on The Flag State implementation and enforcement due to the indirect nature of obligations imposed upon shipmasters through State jurisdiction mechanism under UNCLOS. Accordingly, while Resolution MEPC.384(81) successfully addresses a longstanding regulatory gap in international maritime law, challenges concerning uniform compliance and enforcement among States continue to limit its practical effectiveness